The Meaning Of Love Reflected In Nichola Sparks s Dear John Novel (2006) A Psychoanalytic Analysis - Putri, Hj. Fadilah Harahab, Titis Setyabudi, M.Hum (2017)
This research is purposed to reveal the meaning of love in Dear John novel. The research describes how the character of John is analyzedusing psychoanalytic analysis and to reveal the meaning of lovereflected in the Dear John novel. The type of this research isqualitative study. In analyzing this novel, the researcher usesPsychoanalytic analysis. The primary data source for this research isDear John novel (2006) by Nicholas Sparks. The secondary data ofthis research are taken from any information or all referential datarelated to the novel. The result of the research shows the character ofJohn and the meaning of love in Dear John Novel that include:components of love, types of love.